2004
DOI: 10.1021/jp0401527
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Copper on Reconstructed Pt(100)

Abstract: The growth of copper on the hexagonally reconstructed Pt(100) surface has been studied in UHV by scanning tunneling microscopy (STM). The copper film grows anisotropically and initially almost in a bilayer fashion due to a high diffusion barrier at copper island edges and a reduced mobility on the Cu islands. The substrate reconstruction is lifted only locally by Cu island formation. This lifting leads to an ordered incorporation of platinum excess atoms into the first layer of the growing copper film: At 340 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Of course, this regime can also be studied with the aid of RG flow equations, see e. g. Refs. [28,32,33,113,135,136,151]. We have shown that the mass parameter m 2 σ ∼ σ assumes negative values in this regime.…”
Section: Bosonization and The Momentum Dependence Of Fermion Interactmentioning
confidence: 75%
See 2 more Smart Citations
“…Of course, this regime can also be studied with the aid of RG flow equations, see e. g. Refs. [28,32,33,113,135,136,151]. We have shown that the mass parameter m 2 σ ∼ σ assumes negative values in this regime.…”
Section: Bosonization and The Momentum Dependence Of Fermion Interactmentioning
confidence: 75%
“…RG methods have been extensively employed to study critical behavior in QCD with the aid of NJL-type models, see e. g. Refs. [33,53,55,100,113,[135][136][137][138][139]. Usually these model studies rely on a (partially) bosonized version of the action.…”
Section: A Simple Example and The Fierz Ambiguitymentioning
confidence: 99%
See 1 more Smart Citation
“…Geometry optimizations were performed in redundant internal coordinates without imposing symmetry constraints with the B3LYP functional [13]. The 631-G* basis set [14] was employed for the study of the uncomplexed 2iBu BPMP molecule and the TZVP basis set [15] for the iron complexes. The program NBO 3.0 [16] as implemented in Gaussian 03 was used for subsequent Natural Bond Orbital analyses.…”
Section: Quantum-chemical Calculationsmentioning
confidence: 99%
“…One common theme has been the interaction of metals such as platinum or palladium with copper [1,2,3] and bulk alloys of these elements [4]. We present here an investigation of the structure formed by the interaction of sub-monolayer amounts of platinum with a non-close packed surface of fcc copper; the (110).…”
Section: Introductionmentioning
confidence: 99%